Design of a Flexible Thin-Film Encapsulant with Sandwich Structures of Perhydropolysilazane Layers - Kim, Dajeong; Jeon, Gyeong G.; Kim, Jong H.; Kim, Jincheol; Park, Nochang (ACS Applied Materials and Interfaces, 2022)
Perovskite solar cells (PSCs) have attracted considerable attention due to their excellent photovoltaic properties, but stability issues have prevented their widespread application. PSCs must be protected by encapsulation to extend their lifetime. Here, we show that perhydropolysilazane (PHPS)-based multilayered encapsulation improves the lifetime of PSCs. The PSCs were encapsulated by converting PHPS into silica under vacuum ultraviolet (UV) irradiation. The PHPS-based multilayer encapsulation method achieved a sandwich structure of PHPS/poly(ethylene terephthalate) (PET)/PHPS with a water vapor transmission rate (WVTR) of 0.92 × 10-3 gm-2 d-1 (at 37.8 °C and 100% relative humidity). We then performed a reservoir test of the encapsulated PSCs to confirm the moisture stability of the encapsulation based on PHPS/PET/PHPS barrier films. The cell lifetime remained stable even after 1000 h of ambient-temperature operation. Finally, we analyzed the mechanical flexibility of the PHPS/PET/PHPS multibarrier through bending tests. The multibarrier exhibited high mechanical stability with no large increase in WVTR after bending.
Keywords: Encapsulants; Flexible thin-films; Multibarrier; Organic/inorganic; Organic/inorganic multilayer; Perhydropolysilazane; Solution processable; Thin film encapsulation; Vacuum ultraviolets; Water vapor transmission rate; organic/inorganic multilayer; perhydropolysilazane; perovskite solar cells; solution-processable; thin-film encapsulation; vacuum ultraviolet; water vapor transmission rate